2020
DOI: 10.3390/cryst10050394
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigations on Continuous Fluidized Bed Crystallization for Chiral Separation

Abstract: A recently developed continuous enantioseparation process utilizing two coupled fluidized bed crystallizers is systematically investigated to identify essential correlations between different operation parameters and the corresponding process performance on the example of asparagine monohydrate. Based on liquid phase composition and product crystal size distribution data, it is proven that steady state operation is achieved reproducibly in a relatively short time. The process outputs at steady state are compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 20 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…The other consequence is that the validity of the linear model is limited to shorter operation times. In experiments, a slow contamination of the product has not been found [8]. The purity of the product remained high for operation times of up to 10 h. The experimental purity is slightly lower than the simulated values, which may be explained by the uncertainties in the simulated nucleation rates, or by uncertainties in the measurements.…”
Section: Comparison With the Detailed Model And Experimentsmentioning
confidence: 82%
See 4 more Smart Citations
“…The other consequence is that the validity of the linear model is limited to shorter operation times. In experiments, a slow contamination of the product has not been found [8]. The purity of the product remained high for operation times of up to 10 h. The experimental purity is slightly lower than the simulated values, which may be explained by the uncertainties in the simulated nucleation rates, or by uncertainties in the measurements.…”
Section: Comparison With the Detailed Model And Experimentsmentioning
confidence: 82%
“…The feasibility of the process has been proven in experiments [5,7,8]. It was found that the operation window for successful separation is quite small.…”
Section: Continuous Enantioseparation By Preferential Crystallizationmentioning
confidence: 98%
See 3 more Smart Citations